1971
DOI: 10.1111/j.2044-8260.1971.tb00711.x
|View full text |Cite
|
Sign up to set email alerts
|

The Eysenck Personality Inventory and Social Desirability Response Set with Student and Clinical Groups

Abstract: The EPI was administered to three student groups and to two clinical groups in studies allowing the investigation of Social Desirability(D) effects. Form A of the EPI and the Edwards D scale were completed by 100 students; Form A and the Crowne‐Marlowe D scale by 177 students; Form B and the Crowne‐Marlowe D scale by 175 students; and Form A, including the Lie (L) scale, by 38 potential renal transplant patients and 15 potential renal donors. Negative linear correlations between the Neuroticism (N) scale and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

1972
1972
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 6 publications
6
9
0
Order By: Relevance
“…For both adults (Feather, 1967;Rump & Court, 1971) and children (Miller & Swanson, 1960) the measure of denial was negatively related to IQ score, suggesting that the use of denial is associated with lower levels of cognitive functioning.…”
Section: Defense Mechanisms and Cognitive Developmentmentioning
confidence: 99%
“…For both adults (Feather, 1967;Rump & Court, 1971) and children (Miller & Swanson, 1960) the measure of denial was negatively related to IQ score, suggesting that the use of denial is associated with lower levels of cognitive functioning.…”
Section: Defense Mechanisms and Cognitive Developmentmentioning
confidence: 99%
“…found that the understanding of denial showed a gradual increase across the age span, with the youngest children (5-7.5 years) showing significantly less understanding than the oldest children (10-14 years) and the intermediate group (7.5-10 years) also being intermediate on the understanding measure. Denial has been found to have a negative relationship with general IQmeasures for adults (Feather, 1967;Rump & Court, 1971) and children (Miller & Swanson, 1966). Dollinger, Staley and McGuire (1981) found that favorableness of trait ratings of fifth and sixth graders of a denying character were intermediate between a non-defensive character (most favorable) and a projecting character (least favorable).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive ability as reflected by IQtests is associated with defensive use. Denial has been found to have a negative relationship with general IQmeasures for adults (Feather, 1967;Rump & Court, 1971) and children (Miller & Swanson, 1966). These findings suggest that lower levels of denial usage are indeed associated with higher levels of cognitive functioning and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…In students (i.e. people of above average intelligence), Rump and Court (1971) found a significant negative correlation between Land I.Q. in men, but not in women.…”
Section: St John's Hospitc/ Aylesburymentioning
confidence: 87%